Growth, Optical, Dielectric and Fundamental Properties of L-Arginine Acetate NLO Single Crystals - Editor, Reviewing (Recent Research in Science and Technology, 2010)
Some organic materials exhibit exceeding by large amount of nonlinear property and they are found to be more suitable for device fabrications. Hence, in the present study L-Arginine Acetate (LAA) an organic material, has been extensively studied with regard to the growth and characterization. Single crystals of L-Arginine Acetate (LAA) with good degree of transparency were grown from aqueous solution by slow evaporation technique. Single crystal X-ray diffraction analysis reveals that the crystal belongs to monoclinic system with space group P21. Some fundamental data such as valance electron, plasma energy, Penn gap,Â Â Fermi energy and electronic polarizability of the grown crystal were calculated. The optical absorption studies show that the crystal is transparent in the entire visible region with a cut off wavelength of 240 nm. The optical band gap is found to be 3.75 eV. The dependence of extinction coefficient (K) and refractive index (n) on wavelength has also been reported. Dielectric constant measurements were carried out at different temperatures and frequencies.